Speaker tracking for teleconferencing via binaural headset microphones - Gamper, Hannes; Tervo, Sakari; Lokki, Tapio (Proceedings of the International Workshop on Acoustic Signal Enhancement (IWAENC), 2012)
Speaker tracking for teleconferencing via user-worn binaural headset microphones in combination with a reference microphone array is proposed. The tracking is implemented with particle filtering based on maximum likelihood estimation of time-difference of arrival (TDOA) estimates. An importance function for prior weighting of the particles of silent conferees (i.e., listeners) is proposed. Experimental results from tracking three conferees in a meeting scenario are presented. The use of user-worn microphones in addition to a reference microphone array is shown to improve speaker distance estimation and overall tracking performance substantially. The importance function improved the tracking RMSE by 58% on average. The position tracking RMSE of the proposed method is about 0.11 m.